Chinese Language Teachers' Perceptions of Technology and Instructional Use of Technology: A Path Analysis. (June 2018) - Liu, Haixia; Lin, Chin-Hsi; Zhang, Dongbo; Zheng, Binbin
This study examined internal and external factors affecting pedagogical use of technology among 47 K–12 Chinese language teachers in the United States. Path analysis of the survey data was used to examine the relationships between the teachers' instructional use of technology, on the one hand, and on the other, their perceptions of three internal factors (i.e., technology's usefulness, its ease of use, and subjective norms) and one external factor (i.e., facilitating conditions). The results showed that these teachers' pedagogical use of technology could be predicted by two of the three internal factors (i.e., perceived usefulness and subjective norms) and by the external factor. Additionally, the external factor was found to have a significant influence on both perceived ease of use and subjective norms.